Proverbs and the African tree of life : grafting Biblical proverbs on to Ghanaian Eve folk proverbs - Akoto-Abutiate, Dorothy B. E. A. (Studies in systematic theology (Leiden, Netherlands), 2014)
Proverbs and the African Tree of Life is Dorothy BEA Akoto-Abutiate's argument that African folk sayings must be seen as the full-blown tree on to which the Biblical Proverbs can be "grafted" (that is, taught), be learned, understood and appropriated in Africa